Adherence to Drug Treatment after Stroke and its Association with Patients’ Beliefs about Medicines among Stroke Survivors - Nair, Archana V.; Sylaja, P. N.; Raj, L. Suja (Innovational: Journal of Nursing and Healthcare, 2024)
Aim: Medications for secondary prevention of stroke are important in reducing stroke recurrence in patients who have already experienced a stroke or transient ischemic attack. The objectives of this study were to assess adherence to drug treatment after stroke and to examine association between drug adherence and patients’ beliefs about medicine and illness perception among stroke survivors. Materials and Methods: A descriptive cross-sectional survey was conducted among 105 stroke survivors recruited consecutively from the stroke clinic. Medication adherence was assessed using Hill Bone Medication Adherence Scale. Beliefs about medicine and illness perception were assessed using Beliefs about Medicine Questionnaire (BMQ) and Brief Illness Perception Questionnaire (IPQ). Results: The mean age of the participants was 65 ± 9.89 years. Majority of the participants (67.6%) were males and 24% had recurrent stroke. Assessment of medication adherence shows that 63.8% of stroke survivors had good adherence to medication and 36.2% had poor adherence. Participants who had more positive beliefs about drugs had good medication adherence compared to those with poor adherence (76.5% vs. 51.9%, P = 0.008) and this was statistically significant. Participants with a positive perception of illness had good medication adherence compared to those with negative perception (70.4% vs. 56.9%, P = 0.19), though it was not statistically significant. Conclusion: Knowledge about the importance of drugs can increase patients’ beliefs about medicines, and can improve medication adherence among stroke survivors.